Implications of different guidelines for surveillance after serrated polyp resection in United States of America and Europe - Bleijenberg, Arne; Klotz, Dagmar; Løberg, Magnus; Dekker, Evelien; Adami, Hans Olov; Kuipers, Ernst J.; Holme, Øyvind; Kalager, Mette; Emilsson, Louise; Kleist, Britta; Løvdal, Leif; Regula, Jaroslaw; Løberg, Else M.; IJspeert, Joep; Bretthauer, Michael (Endoscopy, 2019)
Introduction Because individuals with serrated polyps and adenomas are at increased risk of developing new polyps and colorectal cancer (CRC), surveillance after resection is justified. After adenoma resection, most international guidelines are consistent, but recommendations for surveillance after serrated polyp resection vary. The United States Multi-Society Taskforce on CRC (US-MSTF) base surveillance intervals on serrated polyp subtype (traditional serrated adenoma, sessile serrated polyp, hyperplastic polyps), while the European Society of Gastrointestinal Endoscopy (ESGE) guidelines do not take serrated polyp subtype into account. We evaluated the implications of this difference in a primary colonoscopy screening cohort. Methods We included participants from a large colonoscopy screening trial. In a post-hoc simulation, assuming full protocol adherence, we determined the surveillance interval for each subject based on their polyp burden, using the most recent US-MSTF and ESGE guidelines.Results We included 5323 participants, of whom 1228 had one or more serrated polyps. In 5201 of all participants (98 %; Cohen’s kappa 0.90) and in 1106 of those with serrated polyps (90 %; Cohen’s kappa 0.80), both guidelines recommended identical surveillance intervals. Recommendations for a 3-year surveillance interval were identical between the two guidelines. All 122 subjects with discordant recommendations would receive a follow-up colonoscopy after 10 years using ESGE guidance and after 5 years using US-MSTF guidance. Conclusion Despite the different criteria used to determine surveillance after serrated polyp resection, most individuals are recommended identical colonoscopy surveillance intervals whether following the ESGE or US-MSTF guidelines. This suggests that surveillance recommendations do not need to consider the serrated polyp subtype.